2009
DOI: 10.1364/oe.17.011916
|View full text |Cite
|
Sign up to set email alerts
|

Selective excitation of whispering gallery modes in a novel bottle microresonator

Abstract: Selective excitation of spheroidal whispering gallery modes and bottle modes in a robust bottle microresonator fabricated straightforwardly from a short section of optical fiber is demonstrated. Characteristic resonance spectra of long-cavity bottle modes were obtained by using a tapered fiber to excite evanescently bottle microresonator at different points along its axis. Compared to bare-fiber cylindrical resonators, the bottle microresonator results in a 35x increase of the observed Q factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…From the relation between PNJ attributive characteristics and microparticle boundary curvatures, PNJ can be further modulated by changing the microparticle boundary profiles, as show in Fig. 4a for four shape profiles: C-type (circular), P-type (parabolic), H-type (Harmonic-oscillating 25 ) and L-type (linear). The inset at the top of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the relation between PNJ attributive characteristics and microparticle boundary curvatures, PNJ can be further modulated by changing the microparticle boundary profiles, as show in Fig. 4a for four shape profiles: C-type (circular), P-type (parabolic), H-type (Harmonic-oscillating 25 ) and L-type (linear). The inset at the top of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…f C , f P and f H ; ω C , ω P , ω H are respectively the focal points and beam widths of the generated PNJs from these three profiled R-MPCMs. Choice of P-type and H-type profiles, as optimization options, is mainly due to the consideration of developing three-dimensional (3D) high- Ri superlens with controllable heating-and-deforming or self-assembling methods in the future 2527 .
Figure 4( a ) Four boundary profiles for narrowing the transverse beam widths of the PNJs. C-type: circular type, P-type: parabolic type, H-type: harmonic-oscillating type, L-type: linear type.
…”
Section: Resultsmentioning
confidence: 99%
“…Instead of heating and pulling, it has been shown that it is possible to obtain microbottles reversing the mechanical motion; that is, with a “soften and compress” method [21]. …”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…The uniformity of the resulting microbottles is improved when using two CO2 lasers [28]. The “soften-and-compress” [21] method has also been applied to the fabrication of hollow microbottles, adding a moderate pressurization of the capillary to the splicer-based method [29]. For sensing purposes, it might be desirable to make microbottles with very thin walls.…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation